Simon Says: A fun and engaging icebreaker for boosting English language learning - Nisa, Rahmatun; Helmanda, Cut Mawar; Soraya, Nada (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2024)
This study aimed to investigate student perceptions of Simon Says as an icebreaker activity in an English language classroom. Employing a descriptive qualitative approach, the study involved ten students from Grade 11. A purposive sampling method was used to select participants. Data collection instruments included questionnaires administered before and after the implementation of Simon Says icebreaker activities, along with experimental instruction. Questionnaire results indicated that these icebreakers significantly enhanced student enthusiasm and interest in English language learning. Students reported completing the questionnaire accurately and comprehensively. These findings suggest that English language teachers incorporate Simon Says and similar interactive games into their classroom routines. These games can serve as effective icebreakers, fostering a relaxed and engaging learning environment and reducing student anxiety. This encourages greater student participation. This study has implications for both teachers and curriculum developers. Teachers can diversify their teaching methods, while curriculum developers can incorporate such games into teaching materials to enhance student engagement and motivation.